Safe and Efficient Target Singulation with Multi-Fingered Gripper using Collision-Free Push-Stack Synergy - Hyojeong Kim; Younghoon Park; Dohyeon Yoo; Myo-Taeg Lim; Kim, Chang Hwan (Proceedings of 2025 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS 2025), 2025)
Target singulation involves a rearrangement of surrounding obstacles to create space for grasping the target. However, when objects are tightly packed in a confined workspace (i.e., a limited table boundary), it is not easy to relocate obstacles. Using non-prehensile manipulation, such as push, is suitable for creating space when objects are closely placed. However, it can be risky as collisions between objects might unintentionally push them beyond the table boundary. On the other hand, prehensile motion ensures safe relocation of objects. However, the objects that can be safely grasped are limited when the packing density is too high. Thus, it may not find a rearrangement plan for target singulation. To complement both methods, we suggest using collision-free push-stack synergy for rearrangement. Collision-free push prevents objects from moving out of the boundary while efficiently relocating objects and stack creates space in advance to safely push. Furthermore, we propose a modified algorithm of Local Obstacle-based Backward Search (LOBS), which generates a global rearrangement plan using only pick-and-place actions. To evaluate our method, we set up challenging scenarios - with a packing density of 50% and up to 70 objects. Compared to LOBS, the success rate increased significantly with no meaningful increase in planning time. Additionally, Our method outperformed other baselines as well.